Ubiquitous RATs: how resource-aware run-time tests can improve ubiquitous software systems - Merdes, Matthias; Suliman, Dima; Paech, Barbara (Proceedings of the 6th international workshop on Software engineering and middleware, 2006)
In this paper we describe a new approach for increasing the reliability of ubiquitous software systems. This is achieved by executing tests at run-time. The individual software components are consequently accompanied by executable tests. We augment this well-known built-in test (BIT) paradigm by combining it with resource-awareness. Starting from the constraints for such resource-aware tests (RATs) we derive their design and describe a number of strategies for executing such tests under resource constraints as well as the necessary middleware. Our approach is especially beneficial to ubiquitous software systems due to their dynamic nature - which prevents a static verification of their reliability - and their inherent resource limitations.